2012
DOI: 10.2165/11599730-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Pharmacovigilance Algorithms in the ICU Setting

Abstract: These instruments demonstrated similar results for evaluating ADRs in the ICU retrospectively, suggesting that instrument selection with any of the three instruments is reasonable. For concurrent ADR evaluations, there is greater variability in the level of causality obtained among pharmacovigilance algorithms and Kramer displayed better agreement with its comparators. A suggestion for a more definitive concurrent ADR assessment is to use more than one algorithm. This may be challenging in daily clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…This agreement could also be attributed to some extent to the retrospective nature of the literature reports used in the study which is medically validated, and the assessor is unable to discuss the findings with the prescriber. Similar kind of findings was obtained in a study by Kane-Gill et al [10], where the high agreement was observed in the retrospective phase (k=0.794) compared to prospective phase (k=0.635).…”
Section: Goyal Et Alsupporting
confidence: 90%
See 1 more Smart Citation
“…This agreement could also be attributed to some extent to the retrospective nature of the literature reports used in the study which is medically validated, and the assessor is unable to discuss the findings with the prescriber. Similar kind of findings was obtained in a study by Kane-Gill et al [10], where the high agreement was observed in the retrospective phase (k=0.794) compared to prospective phase (k=0.635).…”
Section: Goyal Et Alsupporting
confidence: 90%
“…Among the standardized tools of causal assessment, Naranjo's algorithm is widely in practice. This method has a disadvantage of using the pathological data which might not always be reported/or available [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of nephrotoxins as a plausible cause for AKI is the first consideration in medication management and includes assessment of the temporal sequence between administration and event and alternative explanations . In general, in all phases of AKD, selection of the least nephrotoxic drug and/or avoidance of a nephrotoxin should be the goal.…”
Section: Resultsmentioning
confidence: 99%
“…Combining drugs can also result in important pharmacodynamic drug interactions ; for instance, the administration of some macrolide antibiotics (clarithromycin/erythromycin) with a 3‐hydroxy‐3‐methylglutaryl‐coenzyme‐A (HMG‐CoA) reductase inhibitor (statin) may lead to a greater number of hospitalizations for AKI (from rhabdomyolysis), compared to the administration of azithromycin (a macrolide that does not powerfully inhibit CYP450 enzyme CYP 3A4 and affect clearance of a HMG‐CoA reductase inhibitor) .…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Since several studies accept the categorization of possible or greater as an ADR, then perhaps clinicians artlessly need to comprehend how can these algorithms be implemented at assessing ADRs. 21,22 Thus, expert judgment is typically based on the decisive factor on which algorithms are based so there is a need to develop a high quality assessment method which can accurately set up suitable diagnostic criteria for ADRs. 23 Although Naranjo scale is easily applied, yet in case reports or series of overdose patients, the Naranjo Scale has been stratified to evaluate the probability an event was caused by the ingested drug or therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%